The role of teacher-related factors in enhancing quality service provision in pre-primary schools of Gambella regional state, Ethiopia - Challa Ayale Legede; Tadesse Regassa Mamo; Desalegn Beyene Debelo; Abunu Arega Yismaw (Quality Education for All)
Purpose – The purpose of this study is to examine the crucial factors that impact the quality of pre-primary education in Gambella Regional State, Ethiopia. This study uses a convergent mixed-methods design, integrating both quantitative and qualitative methodologies, to investigate the complex relationship between teacher-related factors and the delivery of quality pre-primary education. This research aims to identify the challenges faced in pre-primary education and provide recommendations to improve the quality of service provision, ultimately fostering positive learning outcomes for children. Design/methodology/approach – This study uses a convergent mixed-methods design, combining quantitative and qualitative methodologies to examine the crucial factors of effective teacher-related elements in providing quality pre-primary education in Gambella Regional State, Ethiopia. Data were collected through surveys, observations, interviews and focus group discussions involving education experts, school principals, teachers and parent–teacher association leaders. Quantitative data was analyzed using inferential statistics, while qualitative data were analyzed thematically. This study integrated the findings from both methodologies to provide a comprehensive understanding of the relationship between teacher-related factors and quality service provision in pre-primary education. Findings – The findings of this study revealed a significant shortage of trained teachers with adequate experience and understanding of early childhood learning. In addition, inappropriate qualifications, insufficient play-based methods and communication shortage between teachers and parents were also identified as critical issues. This study found a strong, positive association between teacher-related factors and quality service provision (coefficient of 0.815 and p-value < 0.001), explaining 51.4% of the variance in service quality. These findings highlight the urgent need for policymakers and educators to prioritize teacher training and professional development in pre-primary education to enhance the quality of pre-primary education and improve learning outcomes for children. Research limitations/implications – This study has some limitations, including the use of a convenience sample and the reliance on self-reported data from teachers, which may be subject to social desirability bias. The findings may not be generalizable to other regions with different contexts, cultures and education systems. Despite these limitations, this study has important implications for policymakers and educators. The findings highlight the critical need for teacher training and professional development in pre-primary education. Practical implications – The findings of this study have important practical implications for policymakers, educators and stakeholders involved in pre-primary education in Gambella Regional State, Ethiopia. This study highlights the urgent need for policymakers to prioritize teacher training and professional development programs in pre-primary education. The findings suggest that improving teacher qualifications, addressing individual learning needs and enhancing play-based methods can positively impact pre-primary education quality. Additionally, this study emphasizes the importance of communication between teachers and parents, as well as effective time management, resource utilization and play-based methods. Social implications – The social implications of this study are significant, as pre-primary education is a critical foundation for a child’s future academic success and overall development. The findings of this study highlight the need for policymakers and educators to prioritize teacher training and professional development in pre-primary education. By addressing the shortage of trained teachers and improving teacher-related factors, pre-primary education quality can be significantly enhanced. This, in turn, can lead to improved cognitive, social and emotional development outcomes for children, setting them up for a lifetime of success and positive contributions to society. Originality/value – This study makes an original contribution to the literature on pre-primary education in Gambella Regional State, Ethiopia, by examining the crucial factors of effective teacher-related elements in providing quality services. The convergent mixed-methods design used in this study provides a comprehensive understanding of the complex interplay between teacher-related factors and the delivery of quality pre-primary education. The findings highlight the significant shortage of trained teachers, inadequate qualifications and deficiencies in addressing individual learning needs and using play-based methods, time management and communication between teachers and parents.